THE INFLUENCE OF ADVERTISING ACTIVITIES ON THE IMAGE OF A HOTEL ENTERPRISE - Вівсюк, Ірина; Мазуркевич, Ірина (SWorldJournal, 2023)
The article analyzed the level of advertising activity in the hotel industry on social networks (Facebook, Instagram, Telegam, Twitter) and each individual's own website. The image coefficient of each researched hotel enterprise was evaluated and calculat